PTH-180 Outcomes of patients who fail initial endoscopic therapy for barrett's related neoplasia. (22nd June 2015) - Haidry, R; Lipman, G; Gupta, A; Dunn, J; Smart, H; Bhandari, P; Willert, R; Fullarton, G; di Pietro, M; Gordon, C; Penman, I; Boger, P; et al.
Abstract : Introduction: Endoscopic therapy with Endoscopic mucosal resection (EMR) followed by Radiofrequency ablation (RFA) is now recommended as first line treatment for patients with Barrett's oesophagus (BE) related neoplasia confined to the mucosa. Method: We examine prospective data from the United Kingdom registry of patients undergoing RFA/EMR for BE neoplasia to examine eventual outcomes of patients who do not have disease reversal at 12 months. All patients were treated with a recommended 12 month treatment protocol where before RFA, visible lesions and nodularity were entirely removed by EMR. Thereafter patients underwent RFA every 3 months until all visible BE was ablated. Biopsies were taken at around 12 months to access for treatment success. Those with residual dysplasia at this stage were offered further treatment and analysed here. Patients with a minimum of 24 months follow up were reviewed. Results: 283 patients (81% male, mean age 70 years, 72% HGD, 24% IMC, 4% LGD) completed the 12 month treatment protocol and the majority 90% (255 patients) had reversal of neoplasia (CR-D) at 12 months with 2–3 RFA treatments. Of these with CR-D only one patient has subsequently progressed to invasive cancer (31 months after treatment). 28 patients had refractory neoplasia and were offered further endoscopic treatment. In these CR-D has been achieved in 67% (19/28) after 1–3 RFA treatments and all are free of neoplasia at median follow up of 46 months form initiating treatment. 3 patients in this cohort of non-responders progressed to invasive disease and the remainder (n = 6) are undergoing on going treatment. Conclusion: The majority of patients with BE neoplasia will achieve successful disease reversal within a structured 12 month treatment program. However in the few that have residual neoplasia at this stage further RFA can be successfully used to eradicate neoplasia. Surgery for those fit remains a definitive treatment choice for the minority who do not respond to initial treatment or progress to invasive disease despite further treatment. All collaborators of the UK RFA registry are acknowledged for their contributions to data collection for this work Disclosure of interest: None Declared.